Linking pollen deposition and snow accumulation on the Alto dell'Ortles glacier (South Tyrol, Italy) for sub-seasonal dating of a firn temperate core - D. Festi; L. Carturan; W. Kofler; G. dalla Fontana; F. de Blasi; F. Cazorzi; E. Bucher; V. Mair; P. Gabrielli; K. Oeggl (The Cryosphere, 2017)
Dating of ice cores from temperate non-polar glaciers is challenging and often problematic. However, a proper timescale is essential for a correct interpretation of the proxies measured in the cores. Here, we introduce a new method developed to obtain a sub-seasonal timescale relying on statistically measured similarities between pollen spectra obtained from core samples and daily airborne pollen monitoring samples collected in the same area. This approach was developed on a 10 m core retrieved from the temperate-firn portion of Alto dell'Ortles glacier (Eastern Italian Alps), for which a 5-year annual/seasonal timescale already exists. The aim was to considerably improve this timescale, reaching the highest possible temporal resolution and testing the efficiency and limits of pollen as a chronological tool. A test of the new timescale was performed by comparing our results to the output (date of layer formation) of the mass balance model EISModel, during the period encompassed by the timescale. The correspondence of the results supports the new sub-seasonal timescale based on pollen analysis. This comparison also allows us to draw important conclusions on the post-depositional effects of meltwater percolation on the pollen content of the firn core as well as on the climatic interpretation of the pollen signal.